2016
DOI: 10.3102/0091732x16660691
|View full text |Cite
|
Sign up to set email alerts
|

Connecting the Present to the Past

Abstract: The authors of this chapter review empirical studies that have been conducted in bilingual education to propose a future research agenda that incorporates the most recent evidence on the effectiveness of bilingual programs, advances in neuroscience, and the body of evidence of the benefits of being bilingual and biliterate. They first describe the historical and sociopolitical precedent of how bilingual education came to play a determinant role in U.S. education. Next, they summarize reviews that have been con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 102 publications
0
8
0
Order By: Relevance
“…Additional evidence for the role of microglia in tau pathology comes from their findings that inhibiting ceramide production with GW4869, knocking down Smase2 expression with small interfering RNAs (siRNAs), or depleting the microglia pool all reduce tau pathology (Asai et al, 2015;Wang et al, 2017). Consistent with these findings, EVs containing P301L mutant tau accelerate pathological tau phosphorylation and oligomer formation but interestingly do not seed mature NFTs in ALZ17 mice (Baker et al, 2016). It is important to note, however, that several tau phosphoepitopes (AT8, AT100, and AT180), which are critical for AD pathology, were undetected and the level of tau in EVs was significantly higher in transgenic mice with pronounced tau pathology (Polanco et al, 2016).…”
Section: Ll Open Accessmentioning
confidence: 94%
“…Additional evidence for the role of microglia in tau pathology comes from their findings that inhibiting ceramide production with GW4869, knocking down Smase2 expression with small interfering RNAs (siRNAs), or depleting the microglia pool all reduce tau pathology (Asai et al, 2015;Wang et al, 2017). Consistent with these findings, EVs containing P301L mutant tau accelerate pathological tau phosphorylation and oligomer formation but interestingly do not seed mature NFTs in ALZ17 mice (Baker et al, 2016). It is important to note, however, that several tau phosphoepitopes (AT8, AT100, and AT180), which are critical for AD pathology, were undetected and the level of tau in EVs was significantly higher in transgenic mice with pronounced tau pathology (Polanco et al, 2016).…”
Section: Ll Open Accessmentioning
confidence: 94%
“…For example, Baker et al (2016) found that vocabulary instruction was the least taught reading component in Spanish or in English in bilingual classrooms, and that students in classrooms that provided better vocabulary instruction also made larger gains on vocabulary measures than students in classrooms with low vocabulary instruction. Regarding the quality of instruction, Tong et al (2008) conducted an experiment to examine whether enhancing a transitional bilingual program (where students learn to read in their native language first before transitioning to English-only instruction) improved reading outcomes for ELs.…”
mentioning
confidence: 99%
“…The academic struggles of English learners have several different causes that might be difficult to tease out, such as low socioeconomic status, low English language proficiency, low vocabulary difficulties in decoding (Baker, Richards-Tutor, Gersten, Baker, & Smith, 2017), and low understanding of procedural mathematics (e.g., understanding addition and subtraction; Orosco, Swanson, O'Connor, & Lussier, 2011). Other potential reasons for poor academic performance can be attributed to poor quality instruction on key elements such as vocabulary (Baker et al, 2017;Tong, Lara-Alecio, Irby, Mathes, & Kwok, 2008), and lack of access to research-based materials in the native language if programs provide native language instruction (Baker, Basaraba, & Polanco, 2016;Vaughn et al, 2006).…”
mentioning
confidence: 99%
“…Social, cultural, and political factors and the availability of resources may shape the types of bilingual programs implemented, how programs are implemented, community perceptions, and ultimately, program outcomes (Baker et al, 2016). The community context in which the bilingual education program operates can significantly contribute to the program's effectiveness.…”
Section: Discussionmentioning
confidence: 99%